2022
DOI: 10.1038/s41586-022-05261-4
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic glassy-metallic transport in an amorphous coordination polymer

Abstract: ParagraphConducting organic materials, such as doped organic polymers, 1 molecular conductors, 2, 3 and emerging coordination polymers, 4 underpin technologies ranging from displays to flexible electronics. 5 Realizing high electrical conductivity in traditionally insulating organic materials necessitates tuning their electronic structure through chemical doping. 6 Furthermore, even materials that are intrinsically conductive, such as single-component molecular conductors, 7,8 require crystallinity for metalli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 56 publications
0
42
0
Order By: Relevance
“…As the present approach may increase the number of independent structural parameters, care should be taken to impose appropriate constraints during the refinement. In the case of two-and one-dimensional nanomaterials, it may be appropriate to apply symmetry constraints within the layer or chain (Beauvais et al, 2021;Xie et al, 2022). For very large or complex models, it may be more appropriate to use this approach to simulate PDFs for different candidate models for comparison with experimental data (Vicchio et al, 2023) or impose constraints based on chemistry or complementary experimental data (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the present approach may increase the number of independent structural parameters, care should be taken to impose appropriate constraints during the refinement. In the case of two-and one-dimensional nanomaterials, it may be appropriate to apply symmetry constraints within the layer or chain (Beauvais et al, 2021;Xie et al, 2022). For very large or complex models, it may be more appropriate to use this approach to simulate PDFs for different candidate models for comparison with experimental data (Vicchio et al, 2023) or impose constraints based on chemistry or complementary experimental data (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This composite PDF is based on a twocomponent model that simulates the contributions from the atomic correlations and local number density (or 'baseline') using separate phases with the same atomic arrangement. This approach has been successfully applied to simulate the PDF for clusters dispersed in solution (Vaughn et al, 2021) and supported on solid materials (Vicchio et al, 2023), as well as low-dimensional nanomaterials (Beauvais et al, 2021) and individual polymeric strands within a glassy conductive polymer (Xie et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27] Very recently, highperformance organic thermoelectric (OTE) materials are obtained by doping of OSCs to increase carrier concentrations and electrical conductivities, which reach device performances comparable to inorganic TEs at low/medium temperature regions. [28][29][30][31][32][33][34][35][36] To achieve efficient chemical doping, frontier molecular orbital energy levels, and charge-transfer process in the dopants/OSCs binary system should be carefully considered. [37][38][39][40][41] Moreover, good miscibility in this binary system is required to obtain high doping levels (Fig.…”
Section: Wuyue Liumentioning
confidence: 99%
“…18. 36,[113][114][115][116][117] The unique p-d electrons overlap and the large bandwidth in these coordination polymers enables intrinsically high electrical conductivity. Without external chemical doping, these coordination polymers showed excellent air stability.…”
Section: Highly Conductive and Air-stable N-type Coordination Polymersmentioning
confidence: 99%
“…More recently, the author [10] showed that the complete N -representability conditions are derivable from convex combinations of higher-particle, constraint matrices. In the past decade approximate conditions have been employed in variational calculations of the 2-RDM to solve significant problems such as the elucidation of the electronic properties of a glassy, highly conductive amorphous polymer [38] and the revelation of exciton condensation in molecular analogs of double-layer graphene [39][40][41][42] (refer to Refs. [43][44][45][46][47][48] for their use in one-particle RDM functional theories).…”
Section: Introductionmentioning
confidence: 99%